Evaluation of school facility management: the case of a high school context in Indonesia - Fitriani, Somariah; Sari, Yessy Yanita; Deni, Rahmad (Intelektual Pustaka Media Utama, 2025)
This study employed the context, input, process, and product (CIPP) model to evaluate the facilities management of a private high school in Jakarta, Indonesia. Participants included teachers, staff, parents, students, and vice principals. Data collection methods encompassed interviews and checklist observations, with participant triangulation used for data validation and verification. Findings indicated a moderate alignment between the context and the objectives of facilities management. While the input, processes, and outputs somewhat addressed stakeholders' educational needs, the school principal effectively facilitated the teaching and learning environment through her roles as a planner, implementer, and supervisor of facilities management. Nevertheless, the school encounters several challenges, such as adapting to the digital era, securing funding, competition, the necessity for a qualified facilities manager, and the need for repairs in several facilities. By identifying the strengths and challenges in the current management practices, including the role of the principal and the impact of digital transformation, the study provides valuable insights for improving facility management. The study recommended the development of a digital facility management system to enhance accessibility for both educators and students.